Studies on Soil Fertility Status of Sri Ganganager District - Kumar, Vinod; Seth, S P (Annals of Arid Zone, 2016)
Studies on soil fertility status of Sri Ganganagar district were undertaken at Soil Testing Laboratory, Sri Ganganagar (Rajasthan). It was observed that on average soils were not problematic with respect to salinity and alkalipity. Soils were low in organic carbon and medium to high in available phosphorus and available Potash. These studies were initiated so that rational schedule of manurial treatments and other cultural practices could be followed. The nutrient status with .respect to N, P and K has been distinguished on Panchayat Samity basis and fertilizer recommendations for various fertility groups have been given.